AN ANALYSIS OF AKRUPAMA SPEAKING SKILLS AMONG GRADE TEN STUDENTS AT STATE SENIOR HIGH SCHOOL 2 TAKALAR - Rahim, Abd; Nurani; Aswati Asri; Nursalam, Nursalam (Universitas Muhammadiyah Makassar, 2026)
Local language learning plays a crucial role in developing students’ language skills while simultaneously preserving local cultural values. This study aims to describe the Akrupama speaking skills of tenth-grade students at Takalar State Senior High School in Makassarese language learning, with a particular focus on pronunciation, intonation, speaking expression, and interpretation. The study employed a quantitative approach with a descriptive research design. The research participants consisted of 34 students from class X MIPA 1, selected using a simple random sampling technique. Data were collected through an Akrupama speaking skills test, classroom observation, and documentation, and were analyzed using descriptive statistical methods. The findings indicate that, overall, students’ Akrupama speaking skills fall into the competent category. A total of 85% of the students achieved scores of 75 or higher, in accordance with the school’s Minimum Mastery Criteria, with a class mean score of 79, which is categorized as good. Aspect-based analysis reveals that pronunciation and intonation are relatively better mastered than speaking expression and interpretation, which still show lower levels of mastery. These results suggest that students’ main challenges are not limited to linguistic competence but also involve affective and performative factors, such as self-confidence and expressive ability. Overall, the study confirms that Akrupama instruction through rupama is effective in enhancing students’ Makassarese speaking skills. The findings underscore the importance of strengthening more varied and performance-oriented instructional strategies to improve the quality of students’ speaking skills in local language learning.